2015
DOI: 10.1097/jom.0000000000000394
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Quality Improvement in Occupational Medicine

Abstract: Residents successfully improved the efficiency of the DOT examination process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Another advantage is that an institutional subscription to the IHI programme provides access to comprehensive QI training and allows tracking the progress of participants [ 24 ]. Some studies adapted IHI modules [ 29 , 32 ] to their local context while other used self-developed content [ 17 19 , 22 , 27 , 28 , 30 ]. The major online modalities used are summarised in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Another advantage is that an institutional subscription to the IHI programme provides access to comprehensive QI training and allows tracking the progress of participants [ 24 ]. Some studies adapted IHI modules [ 29 , 32 ] to their local context while other used self-developed content [ 17 19 , 22 , 27 , 28 , 30 ]. The major online modalities used are summarised in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Most of the included studies reported achieving desired outcomes such as improved QI knowledge and skills [ 14 , 21 , 24 , 25 , 27 , 28 ], positive reaction from participants towards the training [ 17 , 19 , 20 , 32 ], implementation of QI knowledge by participants [ 18 , 29 ] and confidence to use the learned skills in future [ 22 , 28 ]. One study reported no improvement in the measure being tracked [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations